2003
DOI: 10.1038/nature01502
|View full text |Cite
|
Sign up to set email alerts
|

Cold ions in the hot plasma sheet of Earth's magnetotail

Abstract: Most visible matter in the Universe exists as plasma. How this plasma is heated, and especially how the initial non-equilibrium plasma distributions relax to thermal equilibrium (as predicted by Maxwell-Boltzman statistics), is a fundamental question in studies of astrophysical and laboratory plasmas. Astrophysical plasmas are often so tenuous that binary collisions can be ignored, and it is not clear how thermal equilibrium develops for these 'collisionless' plasmas. One example of a collisionless plasma is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 16 publications
2
81
0
Order By: Relevance
“…By using the ISEE-1 relaxation sounder, Etcheto and Saint-Marc (1985) found a plasma component below 30 eV sometimes dominating the plasma sheet boundary layer, reaching densities of 5 cm −3 . More recently, Seki et al (2003) found a similar plasma component in Geotail data from the plasma sheet itself, where we clearly had spurious fields in our example (Sect. 2.2.3).…”
Section: Implications For Other Regionsmentioning
confidence: 89%
“…By using the ISEE-1 relaxation sounder, Etcheto and Saint-Marc (1985) found a plasma component below 30 eV sometimes dominating the plasma sheet boundary layer, reaching densities of 5 cm −3 . More recently, Seki et al (2003) found a similar plasma component in Geotail data from the plasma sheet itself, where we clearly had spurious fields in our example (Sect. 2.2.3).…”
Section: Implications For Other Regionsmentioning
confidence: 89%
“…With Geotail in eclipse, rendering a negative spacecraft potential, Seki et al (2003) were able to detect cold ions coexisting with the hot plasma sheet population. Olsen (1982) made similar measurements of cold ions when two different spacecraft (Applied Technology Satellite 6 and SCATHA) were in eclipse.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, even if the cold ions are exempted from heating, the hot plasma sheet population will prevent the creation of a wake inhibiting measurement of cold ions. Detection of cold ions coexisting with the hot plasma sheet population, as revealed by Olsen (1982) and Seki et al (2003) is therefore not possible with our method.…”
Section: Distribution In Spacementioning
confidence: 99%
“…First, during active times, the ion energy spectrum is generally more complex and may not be represented by a function or by any single function [Christon et al, 1991]. Second, the present approach disregards any coexisting cold ion component even though its density can be comparable to that of the hot component [e.g., Seki et al, 2003]. Therefore, we should keep in mind that those deduced parameters are concerned exclusively with the hot component.…”
Section: Number and Energy Densitiesmentioning
confidence: 99%